Rêves hittites : contribution à une histoire et une anthropologie du rêve en Anatolie ancienne - Mouton, Alice. (Culture and history of the ancient Near East, 2007)
This volume deals with the ancient Anatolian textual evidence on dreams. The book starts with a study of the evidence from different perspectives. The second and third parts are of special interest for anthropologists and historians of religion, as they focus on the various shapes and functions allotted to dreams in Hittite Anatolia. The fourth part assembles the Hittite cuneiform texts in which a dream is either described or mentioned. The texts are given in transliteration and translation, with relevant bibliography. This study makes a significant contribution to our understanding of dream conception in the ancient Near East by providing a systematic edition and analysis of the Hittite testimonies.